An attempt to enhance the methods of obtaining the basic solution of the transportation model by introducing some alteration to such method - Zidan, Abdulsalam (Iraqi Journal of Civil Engineering, 2013)
This research aims to propose a new methodology of obtaining the basic solution of the transportation model, which is one of the operations research. Transportation model aimed to find the economic solution to the plan of allocation of products from production centers to consumption centers. One of the important issues of application the transportation model is the issue of transfer raw materials for construction projects (such as ready-mix concrete) and for which there is usually a set of options for production centers as there is always a group of consumption centers (construction sites). This application was chosen because of the wide use of it and due to its impacts on macroeconomic level. Started by reviewing the current methods of obtaining the basic solution of the transportation model, then the factors that are not taken into account in these methods have been identified and, accordingly, two methods have been developed to obtain the basic solution of the transportation model. The first method depends on the indicator of the biggest costs of transport between the centers, while the second method uses the cost multiplied by the amount transmitted (actual cost) as an indicator to determine the basic solution of the transportation model. Unlike other methods, this method considers all variables mentioned in the objective function. Finally, the proposal method has been illustrated by the use of an empirical example.